2019
DOI: 10.1016/j.ijscr.2019.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Mesocolic hernia following retroperitoneal laparoscopic radical nephrectomy: A case report

Abstract: Highlights An internal hernia after retroperitoneal laparoscopic nephrectomy is rare. Retroperitoneal approach has the risk of making mesocolic defects directly. To prevent internal hernia, we should close the mesenteric defects intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, due to the large wound and the large amount of intraoperative blood loss, the postoperative renal function of the patient is poor, which is not conducive to the postoperative recovery of the patient [ 3 , 4 ]. Retroperitoneal laparoscopic radical nephrectomy (RLRN) has been widely used in the surgical treatment of renal cancer because of its advantages of small wounds, less bleeding, and rapid recovery [ 5 , 6 ]. Although surgical treatment is effective, some renal carcinoma patients still have complications such as peritoneal injury after surgery and in severe cases even relapse, which seriously affects the surgical effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the large wound and the large amount of intraoperative blood loss, the postoperative renal function of the patient is poor, which is not conducive to the postoperative recovery of the patient [ 3 , 4 ]. Retroperitoneal laparoscopic radical nephrectomy (RLRN) has been widely used in the surgical treatment of renal cancer because of its advantages of small wounds, less bleeding, and rapid recovery [ 5 , 6 ]. Although surgical treatment is effective, some renal carcinoma patients still have complications such as peritoneal injury after surgery and in severe cases even relapse, which seriously affects the surgical effect.…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly secondary to peritoneal injury after laparoscopy or open nephrectomy, and most cases occur on the left side. 10–13 Those that have occurred on the right side were seen in the foramen of Luschka. 14 Kar et al 15 reported a case of a primary hernia from the ileum through the parasigmoid sulcus into the retroperitoneal space.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike this patient, retroperitoneal hernias reported share common etiology following a tear in the posterior peritoneum because of trauma like lumbar fractures [ 9 ] and nephrectomy [ 4–7 ]. They could as well be caused by congenital malformations as seen in the pediatric population [ 7 ] . These hernias can be categorized according to the anatomical areas they occur into six groups—paraduodenal, pericecal, intersigmoid, transmesenteric, pelvic and supravesical and those through the foramen of Winslow.…”
Section: Discussionmentioning
confidence: 99%
“…Internal hernias rarely cause intestinal obstruction, accounting for only 4% of all cases of small bowel obstruction. However, they can be fatal with mortality up to 50% if managed untimely, making early diagnosis very vital in preventing gut ischemia [ 11 ] The incidence of retroperitoneal hernia is very low and without specific manifestation, therefore the suspicion index should be high with features of SBO following prior surgery [ 7 ]. Radiographical investigations are key in the initial evaluation and early support diagnosis of retroperitoneal hernia, but these are not without challenges.…”
Section: Discussionmentioning
confidence: 99%